Performance study of electrical discharge machining process in burr removal of drilled holes in Al 7075. Issue 1 (31st December 2016) - John, Pretesh; Davis, Rahul
Abstract: Deburring is the finishing technique that is very essential for the manufacturing of precise components. Although there are various methods to remove burrs but sometimes technology requires new innovative ideas for better outcome irrespective of cost. Deburring with greater efficiency and full automation is a difficult task and this thing leads to use unconventional approaches. This research paper is all about deburring through Electric Discharge Machining process (EDM), which can be useful for finishing materials with very high precision with no men interference. For successful utilization of deburring through EDM, more intensive research including control parameters analysis of the process, is still required. In this research, the drilling operation was done on the specimen to obtain burrs and comparative study was done with different parameters and different electrodes for deburring effectively through EDM. The variable parameters were discharge current, pulse time on and pulse time off and other parameters were remained constant. Material removal rate, tool wear rate and burr height were studied as output parameters to analyse the performance of the combination of the input parameters for burr removal. Grey relational analysis was used to find out the optimal levels of the parameters with copper and brass electrodes respectively. It was found that copper electrode with smaller discharge current and pulse time off and larger pulse time gives better performance and brass electrode with larger discharge current and pulse time off and smaller pulse time on gives better results.